Нечітка арифметика в задачах міжгалузевого балансу - Siavavko, M. S.; Pasichnyk, T. V.; Tymkiv, V. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
To solve problems of interindustry balance, the use of fuzzy-step theory is proposed. Fuzzy logic methods are shown to enable quantitative interpretation of qualitative factors. To find a normal solution to incorrectly-assigned tasks or ill-conditioned systems, the use of the fractionally rational algorithm is offered. Examples of solutions to fuzzy problems are given.